Trypanothione reductase inhibitors: Overview of the action of thioridazine in different stages of Chagas disease - Lo Presti, Maria Silvina (2015)
Thioridazine (TDZ) is a phenothiazine that has been shown to be one of the most potent phenothiazines to inhibit trypanothione reductase irreversibly. Trypanothione reductase is an essential enzyme for the survival of Trypanosoma cruzi in the host. Here, we reviewed the use of this drug for the treatment of T. cruzi experimental infection. In our laboratory, we have studied the effect of TDZ for the treatment of mice infected with different strains of T. cruzi and treated in the acute or in the chronic phases of the experimental infection, using two different schedules: TDZ at a dose of 80 mg/kg/day, for 3 days starting 1 h after infection (acute phase), or TDZ 80 mg/kg/day for 12 days starting 180 days post infection (d.p.i.) (chronic phase). In our experience, the treatment of infected mice, in the acute or in the chronic phases of the infection, with TDZ led to a large reduction in the mortality rates and in the cardiac histological and electrocardiographical abnormalities, and modified the natural evolution of the experimental infection. These analyses reinforce the importance of treatment in the chronic phase to decrease, retard or stop the evolution to chagasic myocardiopathy. Other evidence leading to the use of this drug as a potential chemotherapeutic agent for Chagas disease treatment is also revised.